Management strategies and outcomes in renal transplant recipients recovering from COVID-19: A retrospective, multicentre, cohort study. (April 2022) - Kute, Vivek B.; Ray, Deepak S.; Aziz, Feroz; Godara, Suraj M.; Hegde, Umapati; KumarBT, Anil; Bhalla, Anil K.; Yadav, Dinesh Kumar; Singh, Sarbpreet; Pathak, Vivek; Dalal, Sonal; Bahadur, Madan M.; et al.
Summary: Background: There is an enormous knowledge gap on management strategies, clinical outcomes, and follow-up after kidney transplantation (KT) in recipients that have recovered from coronavirus disease (COVID-19). Methods: We conducted a multi-center, retrospective analysis in 23 Indian transplant centres between June 26, 2020 to December 1, 2021 on KT recipients who recovered after COVID-19 infections. We analyzed clinical and biopsy-confirmed acute rejection (AR) incidence and used cox-proportional modeling to estimate multivariate-adjusted hazard ratios (HR) for predictors of AR. We also performed competing risk analysis. Additional outcome measures included graft loss, all-cause mortality, waiting time from a positive real-time polymerase test (RT-PCR) to KT, laboratory parameters, and quality of life in follow-up. Findings: Among 372 KT which included 38(10·21%) ABO-incompatible, 12(3·22%) sensitized, 64(17·20%) coexisting donors with COVID-19 history and 20 (5·37%) recipients with residual radiographic abnormalities, the incidence of AR was 34 (9·1%) with 1(0·26%) death censored graft loss, and 4(1·07%) all-cause mortality over a median (interquartile range) follow-up of 241 (106–350) days. In our cox hazard proportional analysis, absence of oxygen requirement during COVID-19 compared to oxygen need [HR = 0·14(0·03–0·59); p -value = 0·0071], and use of thymoglobulin use compared to other induction strategies [HR = 0·17(0·03–0.95); p -value = 0·044] had a lower risk for AR. Degree of Human leukocyte antigen (HLA) DR mismatch had the highest risk of AR [HR = 10.2(1·74–65·83); p -value = 0·011]. With competing risk analysis, with death as a competing event, HLA DR mismatch, and oxygen requirement continued to be associated with AR. Age, gender, obesity, inflammatory markers, dialysis vintage, steroid use, sensitization and ABO-incompatibility have not been associated with a higher risk of AR. The median duration between COVID-19 real time polymerase test negativity to transplant was 88(40–145) days (overall), and ranged from 88(40–137), 65(42–120), 110(49–190), and 127(64–161) days in World Health Organization ordinal scale ≤ 3, 4, 5, and 6–7, respectively. There was no difference in quality of life, tacrolimus levels, blood counts, and mean serum creatinine assessed in patients with a past COVID-19 infection independent of severity. Interpretation: Our findings support that the outcomes of KT after COVID-19 recovery are excellent with absence of COVID-19 sequelae during follow-up. Additionally, there does not seem to be a need for changes in the induction/immunosuppression regimen based on the severity of COVID-19. Funding: Sanofi